Collaborative learning in flipped classrooms: enhancing physics education retention in Nigerian secondary schools - Gambari, Amosa Isiaka; Abanikannda, Mutahir Oluwafemi; Abolarinwa, Lucy Folaranmi; Falode, Oluwole Caleb; Uno, Uno (Universitas Negeri Semarang, 2025)
The study examined the impact of three ﬂipped modes of classroom collaborative learning strategies on secondary school students’ retention in Physics in Minna by employing a quasi-experimental design. A sample of 146 students (67 male and 79 female) from four randomly selected Senior Secondary Schools participated. The study formulated three research questions and corresponding hypotheses, tested at a 0.05 significance level. A validated 50-item multiple-choice Physics Achievement Test (PAT) with a reliability coefficient of 0.84 was used for data collection. ANCOVA was employed to analyse the hypotheses. Results indicated that ﬂipped classroom approaches significantly aﬀected students’ achievement and retention. Both male and female students benefited equally from these strategies. The study recommends implementing ﬂipped classroom techniques to enhance Physics instruction in Nigeria, along with training workshops for teachers on blended learning methods.